Rest tremor in advanced essential tremor: a post-mortem study of nine cases. Issue 3 (27th August 2010) - Louis, Elan D; Asabere, Nana; Agnew, Angus; Moskowitz, Carol B; Lawton, Arlene; Cortes, Etty; Faust, Phyllis L; Vonsattel, Jean-Paul G
Abstract : Background: Rest tremor may occur in as many as 30% of essential tremor (ET) patients. It is not clear whether this tremor is a sentinel marker for brainstem Lewy body pathology. Here we report the clinical and post-mortem findings of nine ET cases with upper-extremity rest tremor in the absence of other parkinsonian features. Methods: All brains had a complete neuropathological assessment. Tissue sections from the brainstem and basal ganglia were immunostained with α-synuclein antibody. Results: All cases had longstanding ET (median duration=42 years) with moderate to severe arm tremor. Rest tremor involved both arms in seven (77.8%) cases and one arm in two cases. The rest tremor score was correlated with the total action tremor score (r=0.69, p=0.04). The number of torpedoes was elevated, and Purkinje cells, reduced. Post-mortem changes in the substantia nigra pars compacta (SNc), caudate, putamen and globus pallidum were minimal, and neither Lewy bodies nor Lewy neurites were evident. Conclusions: In nine ET brains with upper-extremity rest tremor, neither Lewy body-containing neurons nor Lewy neurites were found on α-synuclein immunostained sections, and other pathological changes in the basal ganglia were minimal. These data support the notion that isolated rest tremor in longstanding ET is not the expression of underlying Lewy body pathology in the SNc.